2021
DOI: 10.1155/2021/5576362
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Damage Detection of a Bridge under the Uncertain Conditions Based on the Bayesian Framework and Matrix Perturbation Method

Abstract: The bearing of a bridge, as a critical component, is important in the force transformation of the superstructure; however, due to the service condition and repeated impact load, the bearing is prone to be damaged but difficult to detect the damage; the present research has few studies that focused on the damage detection of the structural bearing. Meanwhile, practical engineering is always surrounded by variational environmental conditions, and sometimes, the element and bearing damage both exist in the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Finally, it has to be remarked that field of applicability of the characterization procedure can be extended to all the types of structures for which the dynamic identification is required, independently of the structural typology or of the used material. Another application of the proposed procedure, once the structural characteristics of the frame have been determined, is the detection of the damages on the frames by using continuous monitoring systems [30]. Furthermore, it is worth noting that theoretically there is no limit to the number of unknows but, of course when these variables increase, the timing of the numerical process increase as well.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has to be remarked that field of applicability of the characterization procedure can be extended to all the types of structures for which the dynamic identification is required, independently of the structural typology or of the used material. Another application of the proposed procedure, once the structural characteristics of the frame have been determined, is the detection of the damages on the frames by using continuous monitoring systems [30]. Furthermore, it is worth noting that theoretically there is no limit to the number of unknows but, of course when these variables increase, the timing of the numerical process increase as well.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [179] studied a model simplification technique, through which damage detection based on SBL can be carried out under the condition that the measured degrees of freedom were limited. Li et al [180] reported a combination of the Bayesian theory and perturbation methods to detect structural bearings. The posterior probability density function of the damage parameters was obtained by using the Bayesian damage detection theory, and the calculation cost was saved by using the matrix perturbation method.…”
Section: Bayesian Methodsmentioning
confidence: 99%
“…Based on the Bayesian formula, the posterior probability distribution of a parameter can be calculated as follows [98]:…”
Section: Bayesian Inference-based Model Updating Methodsmentioning
confidence: 99%